2003
DOI: 10.1089/152581603321628296
|View full text |Cite
|
Sign up to set email alerts
|

Infectious Complications in Patients Receiving Mobilization Chemotherapy for Autologous Peripheral Blood Stem Cell Collection

Abstract: The purpose of this retrospective study was to evaluate infectious complications in patients receiving mobilization chemotherapy for stem cell collection prior to autologous peripheral blood stem cell transplantation. An additional goal was to evaluate risk factors associated with the development of infectious complications. At the Medical College of Georgia BMT center, 54 patients were administered mobilization chemotherapy for the purpose of collecting stem cells between June, 1997, and May, 2002. All patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 11 publications
2
8
0
Order By: Relevance
“…For most studies, patient accrual was completed more than 10 years ago. Variable CDAD incidence rates, generally between 1% to 12% for auto-and allo-HSCT recipients, were observed [7][8][9][10][11][12][13]. The most recently published epidemiologic study reported by Chopra et al [13], conducted during the same time period as the present study, observed CDAD rates similar to our results.…”
Section: Discussionsupporting
confidence: 90%
“…For most studies, patient accrual was completed more than 10 years ago. Variable CDAD incidence rates, generally between 1% to 12% for auto-and allo-HSCT recipients, were observed [7][8][9][10][11][12][13]. The most recently published epidemiologic study reported by Chopra et al [13], conducted during the same time period as the present study, observed CDAD rates similar to our results.…”
Section: Discussionsupporting
confidence: 90%
“…Using mobilization chemotherapy results in significant infectious morbidity (Toor et al , 2001). In one report, 26% of patients developed fever or infection during the mobilization phase, and it was not clear that the use of prophylactic antibiotics decreased infectious complications in these patients, most of whom had an indwelling central venous catheter (Jillella et al , 2003).…”
Section: The Role Of Chemotherapy Combined With Growth Factor Mobilizmentioning
confidence: 99%
“…Jillella and colleagues 28 evaluated 54 patients for evidence of infections during the mobilization period for auto-HSCT. These investigators noted only one case of CDAD among 15 instances of infectious complications in the study population.…”
Section: Cdad In Hsct Recipientsmentioning
confidence: 99%